A systematic review of the effects of different resistance training volumes on muscle hypertrophy - Baz-Valle, E.; Balsalobre-Fernández, C.; Alix-Fages, C.; Santos-Concejero, J. (Journal of Human Kinetics, 2022)
The main goal of this study was to compare responses to moderate and high training volumes aimed at inducing muscle hypertrophy. A literature search on 3 databases (Pubmed, Scopus and Chocrane Library) was conducted in January 2021. After analyzing 2083 resultant articles, studies were included if they met the following inclusion criteria: a) studies were randomized controlled trials (with the number of sets explicitly reported), b) interventions lasted at least six weeks, c) participants had a minimum of one year of resistance training experience, d) participants` age ranged from 18 to 35 years, e) studies reported direct measurements of muscle thickness and/or the cross-sectional area, and f) studies were published in peer-review journals. Seven studies met the inclusion criteria and were included in the qualitative analysis, whereas just six were included in the quantitative analysis. All participants were divided into three groups: "low" (<12 weekly sets), "moderate" (12-20 weekly sets) and "high" volume (>20 weekly sets). According to the results of this meta-analysis, there were no differences between moderate and high training volume responses for the quadriceps (p = 0.19) and the biceps brachii (p = 0.59). However, it appears that a high training volume is better to induce muscle mass gains in the triceps brachii (p = 0.01). According to the results of this review, a range of 12-20 weekly sets per muscle group may be an optimum standard recommendation for increasing muscle hypertrophy in young, trained men.